Applied vector analysis - Rahman, M. (CRC Press, 2008)
Presenting the theory and application of vector calculus as it relates to physical problems, Rahman (applied mathematics, Dalhousie U., Canada) and Mulolani (Qatar University) begin with the historical background of vector calculus, proceeding to present information on the algebra of vectors, vector functions of one variable, the role of the delta operator, the theory of surface and volume integrals, and the use of integral theorems. The second edition adds a section on the divergence theorem